Ultralow Threshold Optical Gain Enabled by Quantum Rings of Inverted Type‐I CdS/CdSe Core/Crown Nanoplatelets in the Blue. Issue 8 (15th February 2021) - Delikanli, Savas; Isik, Furkan; Shabani, Farzan; Baruj, Hamed Dehghanpour; Taghipour, Nima; Demir, Hilmi Volkan
Abstract: Achieving low‐threshold optical gain for solution‐processed materials is crucial for their real‐life applications and deployment as gain media. However, the realization of low gain threshold in the blue region has shown to be technically an extremely challenging task using colloidal nanocrystals as a result of fast nonradiative Auger rates in smaller nanocrystals. Here, ultralow‐threshold blue amplified spontaneous emission (ASE) (≈2.7 µJ cm −2 ) accompanied with a large net modal gain coefficient of 360 cm −1 in the blue enabled by blue‐emitting (≈455–465 nm) colloidal quantum rings (QRs) of inverted type‐I CdS/CdSe core/crown nanoplatelets (NPLs) is proposed and demonstrated. The synthesized QRs with controlled crown size outperform the best reported ASE thresholds and net modal gain coefficients from the solution‐processed materials by ≈2.5‐ and ≈4‐fold, respectively, in the similar blue spectral window. Utilizing this QR architecture, it is also shown that the ASE peak can be spectrally tuned by controlling the lateral size of the crown and hence quantum confinement in the lateral direction. These outstanding results support the prospects of these solution‐processed QRs made of 2D hetero‐NPLs in the challenging blue region as colloidal gain. Abstract : Ultralow threshold blue amplified spontaneous emission (ASE) with a large net modal gain coefficient of 360 cm −1 using colloidal quantum rings of inverted type‐I CdS/CdSe core/crown nanoplatelets is achieved in blue. The obtained record‐low ASE threshold presents a significant step toward achieving continuous‐wave pumped lasing in the challenging blue region and support the prospects of these hetero‐nanoplatelets as gain media.